Food cue reactivity in successful laparoscopic gastric banding: A sham-deflation-controlled pilot study - Koenis, Marinka M. G.; Ng, Janet; Anderson, Beth; Stevens, Michael C.; Tishler, Darren S.; Papasavas, Pavlos K.; Stone, Andrea; McLaughlin, Tara; Verhaak, Allison; Domakonda, Mirjana J.; Pearlson, Godfrey D. (Frontiers in Human Neuroscience, 2022)
Laparoscopic adjustable gastric banding (LAGB) offers a unique opportunity to examine the underlying neuronal mechanisms of surgically-assisted weight loss due to its instant, non-invasive, adjustable nature. Six participants with stable excess weight loss (%EWL≥45) completed two days of fMRI scanning 1.5-5 years after LAGB surgery. In a within-subject randomized sham-controlled design, participants underwent (sham) removal of ~50% of the band’s fluid. Compared to sham-deflation (i.e. normal band constriction) of the band, in the deflation condition (i.e. decreasing restriction) participants showed significantly lower activation in the anterior (para)cingulate, angular gyrus, lateral occipital cortex, and frontal cortex in response to food images (p < 0.05, whole brain TFCE-based FWE corrected). Higher activation in the deflation condition was seen in the fusiform gyrus, inferior temporal gyrus, lingual gyrus, lateral occipital cortex. The findings of this within-subject randomized controlled pilot study suggest that constriction of the stomach through LAGB may indirectly alter brain activation in response to food cues. These neuronal changes may underlie changes in food craving and food preference that support sustained post-surgical weight-loss. Despite the small sample size, this is in agreement with and adds to the growing literature of post-bariatric surgery changes in behavior and control regions.